Targeted therapy for high-risk endometrial carcinoma. (September 2012) - Roque, Dana M; Schwartz, Peter E; Santin, Alessandro D
SUMMARY  Type II endometrial cancers exhibit distinct histopathology, underlying pathogenesis and clinical behavior. These high-risk cancers are associated with an aggressive clinical course and a relatively poor prognosis that underscores the need for the development of novel rational therapeutic strategies that exploit their distinct underlying molecular pathway alterations. In this review, we describe the extent of disease burden and molecular characterization of type II endometrial cancers, summarize the historical development to support current standards of care and delineate the most recent preclinical and clinical advances in immunotherapy, cytotoxic agents and small-molecule inhibitors for this disease.